2013
DOI: 10.1007/s13337-013-0168-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative immunogenicity of two peste des petitis ruminants (PPR) vaccines in South Indian sheep and goats under field conditions

Abstract: Peste des petitis ruminants (PPR) is an economically important endemic viral disease of sheep and goats in India, where several different homologous PPR vaccine candidates have been developed. We evaluated the serological response to two vaccine strains, Arasur/87 and Sungri/96, in South Indian cross-bred and native sheep and goats reared under organized and unorganized settings. Animals seronegative (percent inhibition or PI \40) by competitive enzyme-linked immunosorbent assay (c-ELISA) were immunized with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
3
10
0
Order By: Relevance
“…Considerably low morbidity and mortality reported in this study could be due to regular vaccination carried out in the state. It was also elucidated that attenuated PPR vaccine is capable of providing good protection in vaccinated animals which is in accordance with Santhosh et al (2013). On analysis of the data available, maximum number of outbreaks were recorded during 2005, later on outbreaks were less due to regular vaccination programme carried out in the state.…”
Section: Resultssupporting
confidence: 56%
“…Considerably low morbidity and mortality reported in this study could be due to regular vaccination carried out in the state. It was also elucidated that attenuated PPR vaccine is capable of providing good protection in vaccinated animals which is in accordance with Santhosh et al (2013). On analysis of the data available, maximum number of outbreaks were recorded during 2005, later on outbreaks were less due to regular vaccination programme carried out in the state.…”
Section: Resultssupporting
confidence: 56%
“…Further information was sought through the distribution of a questionnaire to the Northern African countries belonging to the Reseau Mediterranéen de Santé Animale (REMESA) 4 network, in order to increase the understanding about the epidemiology of PPR in Northern Africa and to explore possible pathways of potential introduction of the disease into the EU. The information provided within the timeframe of the present opinion is presented in the following section, and, for the answers from some REMESA countries that will be received at a later stage, the analysis will be performed later and the results given back to the REMESA network.…”
Section: Ppr Occurrence In Northern African Countriesmentioning
confidence: 99%
“…It is important to note the in our study both sheep and goats survived PPRV virulent virus challenge post vaccination, indicating an adequate immune response to counter the virus. In an independent study it was reported that Sungri/96 vaccine is equally potent in both sheep and goats [69]. In our study, though there are a few differences in the systems biology across cells (specially the NK cells) between sheep and goats, the co-ordinated response that is inclusive of all the cell subsets was found to be towards induction of strong innate immune response, which is needed for an appropriate adaptive immune response.…”
Section: Discussionmentioning
confidence: 42%